School experiences of young people in conflict with the law at Young People and Adults' Education: the social meaning and the personal sense of the public school - Ronaldo Revejes Pedroso; Gizeli Beatriz Camilo Volpin; Francisco José Carvalho Mazzeu (Universidade Federal do Oeste da Bahia, 2021)
This article presents a discussion about the social meaning and the personal sense of the public school for young people in conflict with the law, according to the understanding of the dialectical historical materialism. Starting from the personal experiences of students from the modality Young People and Adults' Education, we try to understand the problematic of distancing between the social meaning of the school institution and the personal meaning that it has for students, a factor that compromises the pedagogical work. This study was accomplished in a public school in the city of Araraquara/SP. Two young people in conflict with the law were interviewed, one of them is registered in this school and the other one is egressed from the same researched school. The interviews were semi-structured and the obtained results showed that the sense attributed to the school, in general, corresponds to the experiences of socialization and coexistence. We have considered the relevance of this study, since it proposes reflexions to subsidize the practices of teaching work, according to the critical historical Pedagogy.